Principles of Akkadian textual criticism - Worthington, Martin (Studies in ancient Near Eastern records, 2012)
Errors of many kinds abound in Akkadian writings, but this fact's far-reaching implications have never been unraveled and systematized. To attempt this is the aim of this book. Drawing on scholarship from other fields, it outlines a framework for the critical evaluation of extant text and the formulation of conjectural emendations. Along the way, it explores issues at the interface of orthography, textual transmission, scribal education, grammar, literacy, and literary interpretation.--Cover.